2021
DOI: 10.3390/ijms22031139
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Chitosan and ChitosanOligosaccharide on Hepatic Lipogenesis and Lipid Peroxidation, Adipose Lipolysis, and Intestinal Lipid Absorption in Rats with High-Fat Diet-Induced Obesity

Abstract: Chitosan and its derivative, chitosan oligosaccharide (CO), possess hypolipidemic and anti-obesity effects. However, it is still unclear if the mechanisms are different or similar between chitosan and CO. This study was designed to investigate and compare the effects of CO and high-molecular-weight chitosan (HC) on liver lipogenesis and lipid peroxidation, adipose lipolysis, and intestinal lipid absorption in high-fat (HF) diet-fed rats for 12 weeks. Rats were divided into four groups: normal control diet (NC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…COS has recently been found to possess the beneficial effects on HF diet-induced non-alcoholic fatty liver disease in mice [ 22 ]. Recently, our previous study also found that COS supplementation could effectively reduce the levels of TC and TG in the plasma and liver of HF diet-induced obese rats [ 23 ]. Unexpectedly, the present study found that COS supplementation could not significantly reduce the increased levels of TC and TG in the liver of HF diet/STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COS has recently been found to possess the beneficial effects on HF diet-induced non-alcoholic fatty liver disease in mice [ 22 ]. Recently, our previous study also found that COS supplementation could effectively reduce the levels of TC and TG in the plasma and liver of HF diet-induced obese rats [ 23 ]. Unexpectedly, the present study found that COS supplementation could not significantly reduce the increased levels of TC and TG in the liver of HF diet/STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, supplementation with COS in the DF diabetic rats could not significantly decrease the hepatic lipid accumulation. The previous findings suggested that 5% COS may have potential for toxicological side effect in a HF diet-fed condition [ 23 ]. Based on the above reasoning, the findings of present study suggest that 1% COS may be more suitable as a dose for improving diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that high MW chitosan had a higher potential than low MW chitosan in reducing hypercholesterolemia and intestinal disaccharidase activity in STZ-induced diabetic rats [ 9 ]. We further found that both 5% chitosan oligosaccharide (COS) and 5% high MW chitosan (CS) were capable of improving lipid metabolism in an HF diet-fed rat model through different mechanisms [ 15 ]. Our previous study has also shown that CS (high MW) can reduce the plasma fructosamine, leptin, total cholesterol, and HOMA-IR more effectively than low MW chitosan in diabetic rats [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipolysis rate was determined by the measurement of glycerol levels as described previously [ 15 ]. A glycerol detection kit (Randox, Antrim, UK) was used to assay the levels of glycerol in samples.…”
Section: Methodsmentioning
confidence: 99%